2012
DOI: 10.1126/science.1229620
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor and Terminal Subsets of CD8 + T Cells Cooperate to Contain Chronic Viral Infection

Abstract: Chronic infections strain the regenerative capacity of antiviral T lymphocyte populations, leading to failure in long-term immunity. The cellular and molecular events controlling this regenerative capacity, however, are unknown. We found that two distinct states of virus-specific CD8+ T cells exist in chronically infected mice and humans. Differential expression of the T-box transcription factors T-bet and Eomesodermin (Eomes) facilitated the cooperative maintenance of the pool of antiviral CD8+ T cells during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
983
5
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(1,056 citation statements)
references
References 41 publications
61
983
5
7
Order By: Relevance
“…Such a replacement seems to occur in CMV infections 55 . A precursor progeny relation between subpopulations of T-cells that differ in expressing Tbox transcription factors has also been shown in LCMV clone-13 infected mice 72 .…”
Section: Why Are Memory-like Cells Formed In Chronic Infections?mentioning
confidence: 69%
“…Such a replacement seems to occur in CMV infections 55 . A precursor progeny relation between subpopulations of T-cells that differ in expressing Tbox transcription factors has also been shown in LCMV clone-13 infected mice 72 .…”
Section: Why Are Memory-like Cells Formed In Chronic Infections?mentioning
confidence: 69%
“…Interestingly, Tim‐3‐expressing CD8 + T cells retained an ability to produce IFN‐γ similar to other subsets upon stimulation of PMA and ionomycin, and even expressed more mRNA than Tim‐3 − PD‐1 − CD8 + T cells, whereas their expression of TNF‐α was significantly reduced. In agreement with findings regarding exhausted T cells in chronic infection, we also found that aged PD‐1 expressing CD8 + T cells showed T‐bet lo and Eomesodermin (Eomes) hi expression (Paley et al ., 2012) (Fig. 6D).…”
Section: Resultsmentioning
confidence: 94%
“…6D). Because the expression of Eomes has been found to increase in the terminal progeny of exhausted T cells, it seems that Tim‐3 + PD‐1 + cells among aged CD8 + T cells are most similar to the terminal progeny (Paley et al ., 2012). Eomes may function instead of T‐bet to express IFN‐γ in those cells; however, this must be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PD-1 hi Tim-3 ¡ and PD-1 C Tim-3 C CD8 C TIL had higher levels of transcripts for Blimp-1 (encoded by PRDM1) and BATF, transcription factors previously shown to impair T cell proliferation and cytokine secretion and thereby foster T cell exhaustion. 23,24 Moreover, higher expression of Eomes, which is associated with exhausted terminal progeny T cells, and lower levels of T-bet, a marker of robust and functional progenitors, 25 were observed primarily in PD-1 hi Tim-3 ¡ and PD-1 C Tim-3 C CD8 C TIL ( Fig. 2A).…”
Section: Definition Of Hnscc Til By Expression Of Pd-1 and Tim-3mentioning
confidence: 96%